Pengaruh Karakteristik Individu dan Komunikasi Internal terhadap Etos Kerja - Budiyarti, Nelly; Abadi, Hadi Prana; Handayani, Henni Rahayu (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
This research aims to examine the influence of individual characteristics and internal communication on work ethic. The population in this study were teachers at SMAN 04 South Tangerang City. The number of samples in this research was 60 teachers. The type of data in this research is primary data with data collection using a questionnaire. The data analysis method used is correlation analysis and multiple linear regression using SPSS version 20 software. This research shows that individual characteristics and internal communication together have a positive effect on work ethic, individual characteristics have a positive and significant effect on work ethic and communication. Internals have a positive effect on work ethic.